Banking and innovation: A review - Chen Lin; Sibo Liu; Lai Wei (Asian Development Bank Institute (ADBI), 2018)
We summarize the major findings of empirical studies that examine the effect of banking development on innovation and highlight their relative contributions to our understanding of the various roles the banking sector plays in determining innovation. We reassess the effect of banking development and innovation, extending the scope of analysis to more granular dimensions of innovation and to Asian economies where financial markets are less developed. We find that while theoretical implications are generally indefinite about the effect of banking development on innovation, empirical findings are less ambiguous given their distinct focus of sample firms and the underlying channels investigated. The development conditions of financial markets also matter in drawing implications for the effect of financial institutions on innovation. Specifically, when the stock market is relatively less developed, as in most Asian economies, banks play a significant role in financing and promoting innovation. Therefore, it seems plausible for policy makers in these regions to strengthen the development of the banking sector and to improve the depth of the credit market. In this survey, we will summarize the major findings of the empirical studies that examine the effect of banking development on innovation and highlight their relative contributions to our understanding about the various roles that the banking sector plays in determining innovation. Then, we will reassess the effect of banking development and innovation.
Keywords: G2; 330